A STUDY ON THE ABILITY OF THE SECOND SEMESTER ENGLISH DEPARTMENT STUDENTS IN WRITING A PARAGRAPH - Nofria Esti Fauzi; Novitri Novitri; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This study aims to find out the students’ ability in writing a paragraph by the second semester English Department students of Universitas Riau. The population was the second semester English Department students of Universitas Riau, they consisted of three classes: class A, class B, and class C. From 117 students of the population, class A was taken as the sample of this research consist of 39 students. Cluster random sampling was used to choose the sample. The instrument used written test in which students wrote a paragraph. Three topics were provided for students that they can choose to write a paragraph. In analyzing the data,it had been done by calculating the scores of students individually and looking for the mean scores. Based on the result, it was found that the ability of the second semester English Department students in writing a paragraph is in good category with the mean score of 68,3. However, eventhough the students writing scores is in good level, the actual of this score is not that high. This score is considered still low compare to the range from in this level (66-79). There are seven aspects of paragraph writing such as complete sentence, topic sentence, relevant details/supporting sentences, transition word&vocabulary, closing sentence, grammar, and mechanics. After analyzed the data, it was found that two aspects of paragraph writing get in high score in writng a paragraph, they are topic sentence with the mean score of 3,2 and relevant details/supporting sentence with the mean score of 3,1. On the other hand, mechanic aspect of paragraph writing have low score with the mean score of 2,6. Based on this result, it is suggested for students to improve the students’ skill in writing especially for writing paragraph and the students should do more exposure in writing a paragraph. As for the lecturers, it is better to provide more exposure student skill in writing skill by using relevant approaches and techniques to improve students' ability in writing paragraph.Key Words: Writing Paragraph, Study, Ability